Turns of 'fate': Jack Cole, jazz and Bharata Natyam in diasporic translation. Issue 1 (1st March 2019) - Acharya, Rohini; Kaufman, Eric
The musical Kismet opened on Broadway in 1953. This commercially successful play, translated into a film version released two years later, included some of Jack Cole's most widely viewed and popular choreography, which resulted in the exposure of Bharata Natyam to a mass audience through its incorporation into jazz dance. Cole's 'Hindu swing' continues to confound years later, even as Bharata Natyam has ever-increasing prominence in global theatre. This article considers how the form, in migration from Madras to Manhattan, was (and is) materialized and reinscribed, discussing how exoticism and Orientalism are implicated in the mechanisms of this transmogrification. Exploring Cole's involvement with 'Hindu' dance calls into question a range of issues related to the parallel histories of musical theatre dance in the mid-twentieth century, and classical Indian dance in the period of transition from colonial possession to postcolonial independence. We investigate the ways in which Indian culture in diaspora has been translated in our practice, and the ways in which the reception of dance reflects an 'invisibilization' of 'foreign' cultural practice in American popular culture. Collaborating on presenting our juxtaposed experience brings embodied reflection into dialogue with dance scholarship, while also exploring the intersection of these distinct and seemingly discrete dance practices.